2016
DOI: 10.1111/cts.12413
|View full text |Cite
|
Sign up to set email alerts
|

PTTG1 Levels Are Predictive of Saracatinib Sensitivity in Ovarian Cancer Cell Lines

Abstract: Src kinase is recognized as a key target for molecular cancer therapy. However, methods to efficiently select patients responsive to Src inhibitors are lacking. We explored the sensitivity of ovarian cancer cell lines to the Src kinase inhibitor saracatinib to identify predictive markers of drug sensitivity using gene microarrays. Pituitary tumor transforming gene 1 (PTTG1) was selected as a potential biomarker as mRNA levels were correlated with saracatinib resistance, as well as higher PTTG1 protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…The mean expression level of FOXM1 was previously reported to be the highest in the TNBC subtype, which was associated with poor prognosis and reduced survival time in patients with breast cancer (29,30). Notably, PTTG1 is an oncogene that is important for the progression of mitosis in the metaphase-anaphase transition (31,32). Additionally, PTTG1 overexpression is associated with malignancy, particularly thyroid, breast and colorectal carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…The mean expression level of FOXM1 was previously reported to be the highest in the TNBC subtype, which was associated with poor prognosis and reduced survival time in patients with breast cancer (29,30). Notably, PTTG1 is an oncogene that is important for the progression of mitosis in the metaphase-anaphase transition (31,32). Additionally, PTTG1 overexpression is associated with malignancy, particularly thyroid, breast and colorectal carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, PTTG1 was among the eight genes significantly overexpressed in tumor specimens of patients who relapsed on tamoxifen treatment as compared with tumor of patients who did not [ 27 ]. Furthermore, high levels of PTTG1 were found to promote resistance to gefitinib-induced apoptosis in various tumor cell lines [ 28 ] and to be associated with saracatinib resistance in ovarian cancer cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified a number of mechanisms of resistance to inhibitors of the SRC pathway including activation of the mTOR pathway [ 19 ], suppression of autophagy [ 20 ] and secondary mutations in DDR , as well as loss of the tumour suppressor gene NF1 [ 21 ]. It has also been reported that PTTG1 expression is predictive of sensitivity in ovarian cancer cell lines to SRC inhibition with saractinib (AZD0530) [ 22 ]. However this work has not been performed in ovarian cancer models of acquired resistance to SRC inhibitors.…”
Section: Introductionmentioning
confidence: 99%